Empirical and numerical analyses of support requirements for a diversion tunnel at the Boztepe dam site, eastern Turkey - Gurocak, Zulfu; Solanki, Pranshoo; Zaman, Musharraf M. (Elsevier, 2007)
This paper presents the engineering geological properties and support design of a planned diversion tunnel at the Boztepe dam site that contains units of basalt and tuffites. Empirical, theoretical and numerical approaches were used and compared in this study focusing on tunnel design safety. Rock masses at the site were characterized using three empirical methods, namely rock mass rating (RMR), rock mass quality (Q) and geological strength index (GSI). The RMR, Q and GSI ratings were determined by using field data and the mechanical properties of intact rock samples were evaluated in the laboratory. Support requirements were proposed accordingly in terms of different rock mass classification systems. The convergence-confinement method was used as the theoretical approach. Support systems were also analyzed using a commercial software based on the finite element method (FEM). The parameters calculated by empirical methods were used as input parameters for the FEM analysis. The results from the two methods were compared with each other. This comparison suggests that a more reliable and safe design could be achieved by using a combination of empirical, analytical and numerical approaches. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: convergence-confinement method; finite element method; beological strength index; Hoek-Brown failure criterion; rock mass quality; rock mass rating